Assessing the potential for food-based strategies to reduce Vitamin A and iron deficiencies: a review of recent evidence - Ruel, Marie T.; Levin, Carol E. (International Food Policy Research Institute, 2000)
This paper reviews current knowledge and experience with food-based approaches to reduce vitamin A and iron deficiencies. It presents a review of recently published literature, highlights some of the lessons learned, and identifies knowledge gaps and research priorities. Plant breeding strategies are also discussed because of their potential to increase the content of vitamin A and iron in the diet as well as their bioavailability. populations. The same question as that posed in previous reviews decades ago remains at the end of the present review: what really can be achieved with food-based interventions to control vitamin A and iron deficiency? Food based approaches could be an essential part of the long-termglobal strategy to alleviate micronutrient deficiencies but their real potential is still to be explored.